Construction accidents: identification of the main associations between causes, mechanisms and stages of the construction process. Issue 2 (3rd April 2017) - Carrillo-Castrillo, Jesús A.; Trillo-Cabello, Antonio F.; Rubio-Romero, Juan C.
Abstract : Objective . To identify the most frequent causes of accidents in the construction sector in order to help safety practitioners in the task of prioritizing preventive actions depending on the stage of construction. Methods . Official accident investigation reports are analysed. A causation pattern is identified with the proportion of causes in each of the different possible groups of causes. Results . Significant associations of the types of causes with accident mechanisms and construction stages have been identified. Conclusions . Significant differences have been found in accident causation depending on the mechanism of the accident and the construction stage ongoing. These results should be used to prioritize preventive actions to combat the most likely causes for each accident mechanism and construction stage.